If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + -46 = 3(x + 3) + -7 Combine like terms: 12 + -46 = -34 -34 = 3(x + 3) + -7 Reorder the terms: -34 = 3(3 + x) + -7 -34 = (3 * 3 + x * 3) + -7 -34 = (9 + 3x) + -7 Reorder the terms: -34 = 9 + -7 + 3x Combine like terms: 9 + -7 = 2 -34 = 2 + 3x Solving -34 = 2 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -34 + -3x = 2 + 3x + -3x Combine like terms: 3x + -3x = 0 -34 + -3x = 2 + 0 -34 + -3x = 2 Add '34' to each side of the equation. -34 + 34 + -3x = 2 + 34 Combine like terms: -34 + 34 = 0 0 + -3x = 2 + 34 -3x = 2 + 34 Combine like terms: 2 + 34 = 36 -3x = 36 Divide each side by '-3'. x = -12 Simplifying x = -12
| 5x^3-15x^2+x-3=0 | | 6x+6-5x=2x-8+x | | -y^2-26y+120= | | A+9=5a-12 | | (14-y)-(14+20y)= | | 21x-5-18x+4=14x-8-11x+16 | | (5xy^4-7xy^2+4x^2-3)-(-3xy^4+2xy^2-2y+4)=0 | | 2x^3+12x^2+26x-20=0 | | 1/3k-(k+1/5)=1/15(k+3) | | 2y-1=5y+29+1 | | 8(x-1)=3x+5(-1+x) | | 15x+12=-3 | | X-0.2=48 | | 3x+15-5x=20-15x+13x-5 | | Y-(-1)=1/2(x-2) | | 6b+96=0 | | 14y^2+31y-10= | | 12x+16x=112 | | -29=3w-8 | | 3x^3+45x^2+78x=0 | | x^2-x-1=x^2+10x+25 | | x^2-x-1=x^2+10x | | 0.6x+175=140.7 | | -5(t-3)+9t=8t-1 | | 14x-5=7x+9 | | 192/9+134/9= | | 8/5=-15-7z/30 | | 6x-6(6+4x)=26+x | | Y=-2x-5slope | | -39*5= | | X-0.4=276 | | 7x=-12 |